Pattern of Herbal and Dietary Supplement Usage and Conventional Medication Adherence among Patients with Chronic Kidney Disease: A Survey Finding - SN, Sowtali; AA, Mohd Rasani; AS, Mohd. Shah; D, Mohd. Yusoff; CR, Draman; N, Md. Nawi (IIUM Medical Journal Malaysia, 2019)
Introduction: There is widespread use of herbal and dietary supplements worldwide among patients despite robust clinical evidence of its efficacy. This may lead to adverse effects, such as diabetes, hypertension, stroke, cardiovascular risk and kidney problems due to inappropriate self-prescription. This study was performed to determine the prevalence of herbal and dietary supplements usage among patients with chronic kidney disease and its association with the socio-demographic background and the conventional medication adherence. Materials and methods: A survey was conducted among 78 chronic kidney disease patients attending the Nephrology Clinic, Hospital Tengku Ampuan Afzan, Kuantan, Pahang. Data were collected using a questionnaire and analyzed using descriptive statistics, Chi Square Test and Fisher’s Exact Test. The p-value was set to be less 0.05 for its level of significance. Results: Most of the patients aged more than 50 years (89.7%), female (53.8%), unemployed (41%) and from lower socioeconomic earners (75.6%). Only 5.2% of respondents reported using herbal and dietary supplements. There was no association between socio-demographic background with the herbal and dietary supplements usage. Similarly, there was no association between herbal and dietary supplements usage and the conventional medication adherence. Conclusion: This study provides a good baseline on the usage of herbal and dietary supplements use among chronic disease patients. It can be concluded that the level of awareness among the patients is good. Nevertheless, a larger study shall be performed in the future to explore the pattern of association.